2020
DOI: 10.3390/w12020433
|View full text |Cite
|
Sign up to set email alerts
|

Field Study of Mass Balance, and Hydrology of the West Khangri Nup Glacier (Khumbu, Everest)

Abstract: The depiction of glaciers’ dynamics in the high altitudes of Himalaya and the hydrological fluxes therein is often limited. Although sparse seasonal (snow/ice) melt data may be available, dense precipitation networks are not available everywhere, and especially in the highest area, and the assessment of accumulation processes and mass balance may be difficult. Hydrological fluxes are little measured in the high altitudes, and few studies are available covering flow modeling and flow partitioning. Here, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…The authors of [19,24] identified a snow line altitude rise from 5289 m in 1962 to 5471 m in 2011 on the south side of Mount Everest. The authors of [25] reported that on West Kangri Nup Glacier, which is a tributary to the Khumbu Glacier, in the 5400-5500 m range, significant accumulation is no longer being retained through the summer monsoon. The work in [26] considered Rolwaling (Trambau) Glacier and observed an ELA at 5770 m to 5830 m during October 2016-2018.…”
Section: Equilibrium Line and Snow Line Altitudementioning
confidence: 99%
“…The authors of [19,24] identified a snow line altitude rise from 5289 m in 1962 to 5471 m in 2011 on the south side of Mount Everest. The authors of [25] reported that on West Kangri Nup Glacier, which is a tributary to the Khumbu Glacier, in the 5400-5500 m range, significant accumulation is no longer being retained through the summer monsoon. The work in [26] considered Rolwaling (Trambau) Glacier and observed an ELA at 5770 m to 5830 m during October 2016-2018.…”
Section: Equilibrium Line and Snow Line Altitudementioning
confidence: 99%
“…Such seasonal variability indicates different mechanisms of glacier mass loss in the Himalayas. Increased melt conditions in the early winter period, November and December, could enhance velocity, as noted by Bocchiola et al [39], Pelto et al [40] in the eastern Himalaya. During summer, mass losses are more likely to be resulted from increased ablation zone melting, given that precipitation has not been significant [41,42].…”
Section: Linking Surface Velocity Changes With Glacier Mass Balancementioning
confidence: 75%
“…Samples were thawed at room temperature in hermetically sealed tubes. As described in previous papers 78 , 79 , the ratio 18 O/ 16 O of water was analysed using an isotope ratio mass spectrometer (Isoprime, Manchester, UK) interfaced with an on-line automatic system that allows CO 2 /H 2 O equilibration (Multiflow, Isoprime, Manchester, UK). For the analysis of ratio 2 H/ 1 H of water, 200 μl of water together with Hokko bead platinum catalyst (Isoprime) were introduced into a reaction vessel, which was then attached to the online automatic equilibration system and filled with He containing 10% of H 2 .…”
Section: Methodsmentioning
confidence: 99%